B-2+6B=27

Simple and best practice solution for B-2+6B=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for B-2+6B=27 equation:


Simplifying
B + -2 + 6B = 27

Reorder the terms:
-2 + B + 6B = 27

Combine like terms: B + 6B = 7B
-2 + 7B = 27

Solving
-2 + 7B = 27

Solving for variable 'B'.

Move all terms containing B to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 7B = 27 + 2

Combine like terms: -2 + 2 = 0
0 + 7B = 27 + 2
7B = 27 + 2

Combine like terms: 27 + 2 = 29
7B = 29

Divide each side by '7'.
B = 4.142857143

Simplifying
B = 4.142857143

See similar equations:

| 3x/4=6 | | 6x-11x+4=0 | | 13x^2+1-[7(x^2-8)+5]= | | 6x^7-18x^4+24x^6= | | 6+2y-2=9y+13-6y | | 14(t-3)+4t=6(3t+3)-10 | | 2x-5=x+7+2x | | 5fg+g^2=0 | | 2x+-.5=-.75 | | 5fg+g^2=03 | | 7x+15=29 | | 7a+21b=35 | | 3*4=10 | | 5x+7=25-x | | 9x-10=34-2x | | 2xX+-.5=-.75 | | -12x+5=17 | | 7a+21b=36 | | 2y+10x-4=0 | | 2xX+.5=.75 | | 25c^2+80c+64= | | 7a+21b= | | 4(-5x-5)=120 | | 2xT+-.5=-.75 | | 25m^2+4n^2-4n-1= | | x^3-12x^2+36x-32=0 | | 9x(x+8)=4x+32 | | -8-4x=3-7x | | -8.4x=58.8 | | 7a+3=14 | | 2lx+2l=18 | | 5(7-2m)+5=90 |

Equations solver categories